Perspectives of Means Based on Microwave Pulse Compression Technique for Functional Injury of Electronic Systems; 16th Symposium on High Current Electronics, September 19-24, 2010 - Chumerin P. Yu. Pavel Yurievich; Yushkov Y. G. Yuri Georgievich; Slinko V. N. Vladimir Nikolaevich; Hovaev A. Yu.; Sirbu I. A.; Volkov A. A. (High Pover Microwaves, 2010)
Title screen